Intro to Git - Dennison, Justin; Rysdam, Peter van (Packt Publishing, 2024)
Dive into the essentials of version control with Git in this detailed introductory course designed for developers of all levels. Begin with an overview of Git, explaining its importance in modern software development. You'll learn how to install Git, setting a solid foundation to start using this powerful tool. In the initial section, explore setting up a Git repository and making changes to track your project's progress. Through practical demonstrations, learn to add, commit, and manage changes, and efficiently fix mistakes with Git's robust features. This hands-on course equips you with the skills to confidently manage your codebase. The latter part focuses on advanced Git functionalities, such as connecting to remote repositories and understanding branches. You'll learn to create and manage branches for parallel development and workflow efficiency. The course also covers merging techniques, conflict resolution, and seamless work with remote repositories and branches. Finally, dive into collaborative development using GitHub, learning to push changes, pull updates, and collaborate effectively. By the end, you'll be proficient in using Git for version control, ready to implement it in your projects and collaborate with ease.
Online resource; title from title details screen (O'Reilly, viewed June 24, 2024)
Keywords: Git (Computer file); Revision control (Computer science); Open source software; Computer software -- Development; Logiciels libres; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet